Distinguishing affixoid formations from compounds - Ruppenhofer, Josef; Wiegand, Michael; Wilm, Rebecca; Markert, Katja (The 27th International Conference on Computational Linguistics - proceedings of the conference, 2018)
We study German affixoids, a type of morpheme in between affixes and free stems. Several properties have been associated with them – increased productivity; a bleached semantics, which is often evaluative and/or intensifying and thus of relevance to sentiment analysis; and the existence of a free morpheme counterpart – but not been validated empirically. In experiments on a new data set that we make available, we put these key assumptions from the morphological literature to the test and show that despite the fact that affixoids generate many low-frequency formations, we can classify these as affixoid or non-affixoid instances with a best F1-score of 74%.